Pengaruh Kompetensi Guru dan Fasilitas Belajar Terhadap Prestasi Siswa di Pusat Kegiatan Belajar Masyarakat (PKBM) Al-Falah Kelurahan Sumur Batu Kecamatan Bantar Gebang Kota Bekasi - Wahyu Eko Prasetyanto (Universitas Peradaban, 2016)
That the success of learning achievement is determined by several factors. This study tried to examine the relationship between Teacher Competencies and Learning Facilities on Student Achievement. Research conducted at the Community Learning Center (CLC) Al-Falah subdistrict Sumur Batu Bantar Gebang Bekasi, with the number of a sample of 50 students. Data processed by regression techniques using Microsoft Excel 2010. The results showed that both factors (Teacher Competencies and Learning Facility) has an influence on Student Achievement, each with a coefficient of 0.472 and 0.482, and simultaneously influence by 76%, with a coefficient of 0.762 Goodness of Fit.